Current attitudes toward drug checking services and a comparison of expected with actual drugs present in street drug samples collected from opioid users - James A. Swartz; Marya Lieberman; A. David Jimenez; Mary Ellen Mackesy-Amiti; Heather D. Whitehead; Kathleen L. Hayes; Lisa Taylor; Elizabeth Prete (Harm Reduction Journal, 2023)
Abstract Background The opioid epidemic continues to be associated with high numbers of fatalities in the USA and other countries, driven mainly by the inclusion of potent synthetic opioids in street drugs. Drug checking by means of various technologies is being increasingly implemented as a harm reduction strategy to inform users about constituent drugs in their street samples. We assessed how valued drug checking services (DCS) would be for opioid street drug users given the ubiquity of fentanyl and related analogs in the drug supply, the information they would most value from drug checking, and compared expected versus actual constituent drugs in collected samples. Methods A convenience sample of opioid street drug users (N = 118) was recruited from two syringe service exchange programs in Chicago between 2021 and 2022. We administered brief surveys asking about overdose history, whether fentanyl was their preferred opioid, and interest in DCS. We also collected drug samples and asked participants what drug(s) they expected were in the sample. Provided samples were analyzed using LC–MS technology and the results compared to their expected drugs. Results Participants reported an average of 4.4 lifetime overdoses (SD = 4.8, range = 0–20) and 1.1 (SD = 1.8, range = 0–10) past-year overdoses. A majority (92.1%) believed they had recently used drugs containing fentanyl whether intentionally or unintentionally. Opinions about the desirability of fentanyl were mixed with 56.1% indicating they did not and 38.0% indicating they did prefer fentanyl over other opioids, mainly heroin. Attitudes toward DCS indicated a general but not uniform receptiveness with a majority indicating interest in DCS though sizeable minorities believed DCS was “too much trouble” (25.2%) or there was “no point” in testing (35.4%). Participants were especially inaccurate identifying common cutting agents and potentiating drugs such as diphenhydramine in their samples (sensitivity = .17). Conclusions Results affirmed street drug users remain interested in using DCS to monitor their drugs and such services should be more widely available. Advanced checking technologies that provide information on the relative quantities and the different drugs present in a given sample available at point-of-care, would be most valuable but remain challenging to implement.